Smart Marketing, A Growing Economy: an Analysis of The Role of Marketing Innovation in the 4.0 era - Sampeliling, Alexander; Rauf, Abdul; Adhimursandi, Doddy (Nomico, 2025)
In the era of Industry 4.0, marketing innovation has become a crucial factor for business sustainability and economic acceleration, especially for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of marketing innovation in driving business growth and contributing to economic development. Using a quantitative approach with survey data from selected MSMEs, the research applied statistical analysis through SPSS to examine the relationship between marketing innovation and business performance indicators such as sales growth, customer loyalty, and market expansion. The findings reveal that digital marketing tools, such as social media platforms, e-commerce integration, and personalized content, significantly enhance business outcomes. However, challenges such as low digital literacy, financial constraints, and limited access to technology remain critical barriers to wider adoption. The study concludes that marketing innovation not only improves individual business competitiveness but also has the potential to boost economic vitality. Policy recommendations include strengthening digital training programs and infrastructure to support innovation among MSMEs.